PENYULUHAN PEMBERDAYAN IBU RUMAH TANGGA DALAM MENGATUR GIZI BALITA DAN ANAK DI DESA BUKIT AGUNG KECAMATAN KERINCI KANAN KABUPATEN SIAK [EMPLOYMENT HOUSEHOLD MOTHER MANAGEMENT IN GUIDING NUTRITION FOR BABY UNDER FIVE YEARS AND CHILDREN IN BUKIT AGUNG VILLAGE, KERINCI KANAN DISTRICTS, SIAK REGENCY] - Latifa Siswati; M. Rizal; Ambar Tri Ratnaningsih; Riski Novera Yenita (Universitas Pelita Harapan, 2019)
Households play an important role in regulating family health by regulating the nutrition intake of toddlers and children. Sources of food available in the yard can be used to be a healthy and nutritious food by processing these ingredients properly. It needs to empower housewives in managing nutrition and toddlers by utilizing food sources in the vicinity. The purpose of dedication is 1) Empowerment of housewives in regulating child and child nutrition, 2) Increasing knowledge and skill of housewives in processing food that exist in home yard into healthy and nutritious food. The activity was held in Bukit Agung Village, Kerinci Kanan District, Siak Regency, Riau Province. The method used is counseling and training. The technique of selecting the participants is done by purposive sampling, ie farmers who use their home yard for medicinal plants, food crops, horticulture, fish and others that can potentially meet family needs. The results of this activity indicate that after counseling there is increasing knowledge of housewives about nutritious food source for toddler and child equal to 20,83% and nutritional benefit for growth and development of child equal to 25%. Once given training housewives can take advantage of available food sources in the yard of her house into a variety of healthy and nutritious foods such as pudding and meatballs.Bahasa Indonesia Abstrak: Ibu rumah tangga memegang peran penting dalam mengatur kesehatan keluarga dengan mengatur asupan gizi balita dan anak. Sumber pangan yang tersedia di pekarangan rumah dapat dimanfaatkan menjadi makanan yang sehat dan bergizi dengan mengolah bahan makan tersebut dengan baik. Perlu adanya pemberdayaan ibu rumah tangga dalam mengatur gizi dan balita dengan memanfaatkan sumber pangan di sekitarnya. Tujuan pengabdian adalah 1) Pemberdayaan ibu rumah tangga dalam mengatur gizi balita dan anak, 2) Meningkatkan pengetahuan dan ketrampilan ibu rumah tangga dalam mengolah bahan pangan yang ada di pekarangan rumah menjadi makanan yang sehat dan bergizi. Kegiatan dilaksanakan di Desa Bukit Agung Kecamatan Kerinci Kanan Kabupaten Siak Provinsi Riau. Metode yang digunakan adalah penyuluhan dan pelatihan. Teknik pemilihan peserta dilakukan secara purposive sampling yaitu petani yang memanfaatkan pekarangan rumahnya untuk tanaman obat, tanaman pangan, hortikultura, ikan dan lainnya yang berpotensi dapat memenuhi kebutuhan keluarga. Hasil dari kegiatan ini menunjukkan bahwa setelah penyuluhan ada peningkatan pengetahuan ibu rumah tangga tentang sumber pangan yang bergizi bagi balita dan anak sebesar 20,83% dan manfaat gizi bagi tumbuh dan kembang anak sebesar 25%. Setelah diberi pelatiah ibu rumah tangga dapat memanfaatkan sumber pangan yang tersedia di pekarangan rumahnya menjadi aneka makanan yang sehat dan bergizi seperti puding dan bakso.